A randomized controlled trial of the effect of music during cesarean sections and the early postpartum period on breastfeeding rates - Saifon Chawanpaiboon (2022)
Objective: The objective of this research was to study the role of music listening by mothers during a cesarean section and the postpartum period to achieve exclusive breastfeeding in the first 6 months. Methods and Study Design: This was a prospective, observational, randomized controlled trial study. A total of 185 singleton pregnant women, in at least 37 weeks of gestation, who were appointed for elective cesarean sections, were recruited. They were randomized into three groups, including pregnant women who did not listen to music (Group 1), listened to music during cesarean section (Group 2), and listened to music during cesarean section and the postpartum room for the first 2 days (Group 3). The breastfeeding results of all three groups were followed up at 7 days, 14 days, and then at months 1, 2, 3, and 6. Results: Success in exclusive breastfeeding among Groups 1, 2, and 3 and Groups 1 and 2 + 3 was not different in every lactating period (7 days-6 months). From subgroup analysis, mothers who listened to music in a private ward had more success in exclusive breastfeeding than those in a common ward. Mothers who listened to music and had an income of <20,000 baht, an educational level lower than university, planned the pregnancy, had their first pregnancy, and stayed in a private ward had more successful exclusive breastfeeding in a 6-month period than those mothers who did not listen to music, and the difference was statistically significant. Conclusions: Music listening by mothers during a cesarean section and in the postpartum ward did not enhance exclusive breastfeeding during the first 6 months of the postpartum period. However, from subgroup analysis, mothers who listened to music in a private ward had more success in exclusive breastfeeding than those in a common ward. Thai Clinical Trials Registry number was TCTR20180712001.